Peri-operative transfusion risk in classic bladder exstrophy closure: Results from a national database review. Issue 4 (August 2016) - Preece, Janae; Asti, Lindsey; Ambeba, Erica; McLeod, Daryl J.
Summary: Objective: Classic bladder exstrophy (CBE) is one of the most complex pediatric urologic conditions, with patients often requiring multiple procedures throughout their lives. Patients undergoing these complex surgeries may require blood transfusion, exposing them to the risks of transfusion including antibody reactions, transmission of infectious diseases, and transfusion-related immunomodulation. We sought to determine the prevalence of and risk factors for peri-operative transfusion in patients undergoing closure for CBE. Because of the complexity of CBE management, we hypothesized that a significant number of patients undergoing closure of CBE would require peri-operative transfusion. Method: Patients undergoing CBE closure between 2012 and 2014 were retrospectively identified by Current Procedure Terminology codes from The National Surgical Quality Improvement Program Pediatric database, which includes data from 64 participating hospitals. Patient demographics, pre-operative characteristics including comorbidities, intra-operative characteristics, and post-operative outcomes were analyzed for associations with transfusion requirement intra-operatively or in the first 72 h post-operatively. Results: Seventy-eight patients met our criteria, of whom 45 (57.7%) underwent transfusion. Patient characteristics and outcomes are noted in theTable . There was no difference between the groups in terms of age or gender. Patients who underwent transfusion were more likely to be over 3 days of age than those who did not (93.3% versus 75.8%; p  = 0.046). Transfused patients were also more likely to have undergone osteotomy (82.2% versus 48.5%; p  = 0.002), had an external fixation (46.7% versus 6.1%; p  < 0.001), had longer median operative times (447 versus 295 min; p  < 0.001), and had longer median post-operative lengths of stay (LOS) (35 versus 17 days; p  = 0.003). There was no difference between the groups in terms of pre-operative risk factors or post-operative complications. Conclusions: A significant number of patients undergoing CBE closure required transfusion in the peri-operative period (57.7%). Patient characteristics found to have a higher rate of transfusion included osteotomy, external fixation, increased operative times, and longer post-operative LOS. In children undergoing closure for CBE, a large number require transfusion. The rate of transfusion is greater in older children and children undergoing osteotomy. Although osteotomy has a potentially important clinical role, especially in older patients, this study emphasizes the need for proper family counseling to include the increased likelihood of a blood transfusion and the risks associated with blood transfusion if osteotomies are performed. Table Patient characteristics and outcomes of patients undergoing closure for CBE requiring peri-operative transfusion and those not requiring transfusion.   Transfusion No transfusion p -value n % n % Total 45   33     Neonate 9 20.0 15 45.5 0.016 Age (days) a 200 35–557 8 4–382 0.050 Age >3 days 42 93.3 25 75.8 0.046 Female 22 48.9 16 48.5 0.972 Male 23 51.1 17 51.5 Caucasian 35 77.8 21 63.6 0.170 Non-Caucasian 10 22.2 12 36.4 Osteotomy 37 82.2 16 48.5 0.002 External fixation 21 46.7 2 6.1 <0.001 Total operation time (minutes) a 447 373–534 295 238–371 <0.001 Post-operative length of stay (days) a 35 15–50 17 6–31 0.003 Post-operative complication 25 55.6 16 48.5 0.536 Bold p -values indicate a significant result at p  < 0.05. a Values are expressed as median (interquartile range).